2010
DOI: 10.1590/s0004-27492010000200005
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study demonstrating the effect of 5% povidone-iodine application for anterior segment intraocular surgery in Paraguay

Abstract: Purpose: To determine the conjunctival bacterial flora in cataract surgery patients and the effect of presurgical irrigation with 5% povidone-iodine solution. Methods: Three samples from the inferior conjunctival fornix of the eye to be operated were obtained at baseline before washing (T 0 ) with 10 ml 5% povidone-iodine solution, immediately after washing (T 1 ), and upon completion of surgery (T 2 ). Bacteria from the samples were inoculated in blood agar, chocolate agar, and thioglycolate broth. Results: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
1
14
0
2
Order By: Relevance
“…In U.S. and European studies, a high concentration (5% or 10%) of PVP-I was suggested to effectively lower the incidence of postoperative endophthalmitis5141516. However, in a Japanese study, 0.1–1% PVP-I was found to be more rapidly bactericidal than a full-strength solution (10%)17.…”
Section: Discussionmentioning
confidence: 97%
“…In U.S. and European studies, a high concentration (5% or 10%) of PVP-I was suggested to effectively lower the incidence of postoperative endophthalmitis5141516. However, in a Japanese study, 0.1–1% PVP-I was found to be more rapidly bactericidal than a full-strength solution (10%)17.…”
Section: Discussionmentioning
confidence: 97%
“…Quiroga et al [29] investigated the efficacy of 5% PVI in anterior segment intraocular surgery; 221 patients were studied. It was determined that conjunctival irrigation with a 5% PVI solution can effectively reduce conjunctival flora (by 60.8%) and recommended its use as a means of preventing postoperative endophthalmitis following cataract surgery.…”
Section: Povidone-iodine In Preoperative Prophylaxismentioning
confidence: 99%
“…Various studies reveal, most cases are due to bacteria entering the eye at the time of surgery [19],so it is believed that the chief source of infection is usually the patient's own microbial flora from the conjunctiva, eyelids and lacrimal sac [20].The most commonly implicated organisms causing endophthalmitis worldwide are Coagulase negative staphylococci (33-77%), Staphylococcus aureus (10-21%), Streptococci (9-19%), Gram negative bacteria including Pseudomonas aeruginosa (6-22%) and fungi (up to 8%) [21]. An evidence-based review of the literature concluded that preoperative povidone-iodine prophylaxis was the single most effective means for reducing the risk for postoperative endophthalmitis (decreasing microbial load up to 91%) [22,23].Still a considerable number of positive culture have been obtained from the post-surgery patients in spite of the use of povidone-iodine in many studies ,to name a few such as those done by Quiroga et al [24] and Kumar et al [25], emphasizing other methods should be sought to further reduce conjunctival flora. .…”
Section: Discussionmentioning
confidence: 99%